C++ High Performance : Boost and optimize the performance of your C++17 code. - Andrist, Björn (Packt Publishing, 2017)
C++ is a highly portable language and can be used to write complex applications and performance-critical code. It has evolved over the last few years to become a modern and expressive language. This book will guide you through optimizing the performance of your C++ apps by allowing them to run faster and consume fewer resources on the device ...